Advances in Detecting Low Prevalence Somatic TERT Promoter Mutations in Papillary Thyroid Carcinoma - da Costa, Vitor Rodrigues; Bim, Larissa Valdemarin; Pacheco e Silva, Luiza Dornelles Penteado; Colloza-Gama, Gabriel Avelar; Bastos, André Uchimura; Delcelo, Rosana; Oler, Gisele; Cerutti, Janete Maria (Frontiers in Endocrinology, 2021)
Background Two recurrent TERT (telomerase reverse transcriptase) promoter mutations, C228T and C250T, have been reported in thyroid carcinomas and were correlated with high-risk clinicopathological features and a worse prognosis. Although far more frequent in the poorly differentiated and undifferentiated thyroid cancer, the TERT promoter mutations play a significant role on PTC recurrence and disease-specific mortality. However, the prevalence varies considerably through studies and it is uncertain if these differences are due to population variation or the methodology used to detect TERT mutations. In this study we aim to compare three different strategies to detect TERT promoter mutations in PTC. Methods DNA was isolated from formalin-fixed paraffin-embedded (FFPE) specimens from 89 PTC and 40 paired lymph node metastases. The prevalence of the hot spot TERT C228T and C250T mutations was assessed in FFPE samples using TaqMan SNP genotyping assays. Random samples were tested by Sanger Sequencing and droplet digital PCR (ddPCR). Results In general, 16 out of 89 (18%) PTC samples and 14 out of 40 (35%) lymph node metastases harbored TERT promoter mutations by TaqMan assay. Sanger sequencing, performed in random selected samples, failed to detect TERT mutations in four samples that were positive by TaqMan SNP genotyping assay. Remarkably, ddPCR assay allowed detection of TERT promoter mutations in six samples that harbor very low mutant allele frequency (≤ 2%) and were negative by both genotype assay and Sanger Sequencing. Conclusion This study observed a good concordance among the methodologies used to detect TERT promoter mutations when a high percentage of mutated alleles was present. Sanger analysis demonstrated a limit of detection for mutated alleles. Therefore, the prevalence of TERT promoter mutations in PTC may be higher than previously reported, since most studies have conventionally used Sanger sequencing. The efficient characterization of genetic alterations that are used as preoperative or postoperative diagnostic, risk stratification of the patient and individualized treatment decisions, mainly in highly heterogeneous tumors, require highly sensitive and specific approaches.